Constructions in learner language - Martínez Vázquez, Montserrat (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper examines the degree to which learners’ L1 typology may affect the comprehension and production of L2 constructions. It has been suggested that English makes more use of constructional meaning than other languages (Goldberg, 2006: 120). Spanish learners of English have been found to face difficulties interpreting constructional meaning when it does not match the verb sense. One of the reasons for this failure may be the lack of a comparable construction in their native language (Martínez Vázquez, 2004). The caused-motion construction is common to satellite-framed languages but almost inexistent in verb-framed languages. I will hypothesize that learners of English with a source language that has a similar construction will make a better use of constructional meaning than learners whose native language does not contain this form-meaning correspondence. In order to test this hypothesis I made an extensive search for Motion verbs in the ICLE (International Corpus of Learner English). The writing produced by native speakers of three satellite-framed languages (German, Dutch and Swedish) was contrasted with the production of native speakers of verb-framed languages (Spanish, French and Italian). The results supply evidence of how the typology of the source language may facilitate or hinder the learning process.